Ji yu Azure de zi dong ji qi xue xi = Practical automated machine learning on Azure / = Practical automated machine learning on Azure - Mukunthu, Deepak; Shah, Parashar; Tok, Wee-Hyong (Zhongguo dian li chu ban she = China Electric Power Press Ltd., 2020)
Detailed summary in vernacular field.
880-04;O'Reilly Media, Inc. shou quan chu ban
Keywords: Windows Azure; Machine learning; Artificial intelligence